Od jednej Ewangelii Chrystusa do czterech Ewangelii Kościoła - Królikowski, Janusz (Vox Patrum, 2019)
FROM ONE GOSPEL OF CHRIST TO FOUR GOSPELS OF THE CHURCH (Summary) The Early Church had to deal with numerous issues while fulfilling Its mission. One of them was the question of formulating the unambiguous list of canonical writings, especially Gospels, which would serve as a foundation for shaping of Its life and Its doctrine. The problem was even more complicated since one Gospel taught by Jesus before long became the source for manifold writings which aspired to become Its authentic testimony. As a result, a lot of Gospels appeared. The question of making the right choice became the source of actions and the subject of debates held by Marcion of Sinope, Justin Martyr, Tatian the Syrian, and finally Saint Irenaeus. The latter, most notably contributed to the codification of all four, now-canonical Gospels by Matthew, Mark, Luke and John (one Gospel in four variations) as a rule for Church life. The article includes the attempt to recreate the process which took place in the 2nd century.